Foamed aluminum material, preparation method thereof and application of foamed aluminum material in electromagnetic shielding
A foamed aluminum material with specific alloy elements and a controlled preparation process achieves enhanced electromagnetic shielding performance and mechanical properties, addressing the cost issue of thickening in strong magnetic fields.
Patent Information
- Application Number
- CN202411184977.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-27
- Publication Date
- 2024-12-24
AI Technical Summary
Aluminum foam materials require thickening in strong magnetic fields to meet electromagnetic shielding performance requirements, which is costly.
A foamed aluminum material composed of specific alloy elements (magnesium, cerium, neodymium oxide, boron carbide, silicon, and carbon) is prepared through a process involving mixing, heat treatment, bubble introduction, and aging treatment to achieve uniform bubble distribution and enhanced mechanical properties.
The resulting foamed aluminum exhibits excellent electromagnetic shielding performance across a wide band (10 kHz to 40 GHz) with high specific strength, weather resistance, and corrosion resistance, suitable for electronic equipment, communication equipment, aerospace, and military applications.
Smart Images

Figure BDA0005013256800000061 
Figure BDA0005013256800000071 
Figure BDA0005013256800000081
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of electromagnetic shielding materials, and in particular to a foamed aluminum material and a preparation method thereof and application thereof in electromagnetic shielding. Background Art
[0002] Foamed aluminum is an aluminum-based metal material containing a large number of closed voids that is made by adding additives to pure aluminum or aluminum alloy and undergoing a foaming process. It has the characteristics of both metal and bubbles and is characterized by low density, strong impact absorption, high temperature resistance, good fire resistance, corrosion resistance, sound insulation and noise reduction, low thermal conductivity, high electromagnetic shielding, strong weather resistance, filtering ability, easy processing, easy installation, high forming precision, and surface coating. It is widely used in transportation, construction machinery, electronic communications, aerospace, environmental protection and other fields.
[0003] In recent years, a series of studies on aluminum foam materials have found that it has excellent performance in the field of electromagnetic shielding. The aluminum foam materials prepared by adding specific alloy elements and using specific processes have good electromagnetic shielding effectiveness in almost all bands. However, aluminum foam materials still need to be thickened in a strong magnetic field environment to meet certain performance requirements, which is costly. Summary of the invention
[0004] The technical problem to be solved by the present invention is to provide a foam aluminum material and a preparation method thereof. The obtained foam aluminum material performs excellently in the field of electromagnetic shielding, is weather-resistant and corrosion-resistant, has high specific strength, and is a perfect alternative material in the field of electromagnetic shielding.
[0005] The technical problem to be solved by the present invention is achieved by adopting the following technical solutions:
[0006] The first object of the present invention is to provide a foamed aluminum material comprising the following components in weight percentage:
[0007] Magnesium 3-10%, cerium 0.1-0.2%, neodymium oxide 1-1.5%, boron carbide 0.02-0.1%, silicon 3-8%, carbon 0.02-0.08%, and the balance is aluminum.
[0008] The second object of the present invention is to provide a method for preparing the foamed aluminum material, comprising the following steps:
[0009] (1) mixing aluminum oxide and silicon carbide uniformly and then heat treating them in an inert atmosphere;
[0010] (2) heating the aluminum ingot in an inert atmosphere until it is melted, then adding the heat-treated aluminum oxide and silicon carbide, keeping the temperature at 700-800°C for 10-15 minutes, then adding the magnesium ingot, and continuing to keep the temperature at 700-800°C for 10-15 minutes, and finally adding cerium, boron carbide and neodymium oxide, and mixing them thoroughly to obtain an alloy liquid;
[0011] (3) introducing compressed air into the molten alloy liquid, stirring to uniformly distribute the bubbles, then cooling to 650-670° C. at a cooling rate of 5-10° C. / min and keeping the temperature for 10-15 min, and continuing to cool to room temperature to obtain a foam aluminum preform;
[0012] (4) The foam aluminum preform is subjected to a solid solution treatment and an aging treatment to obtain foam aluminum.
[0013] The third object of the present invention is to provide application of the foam aluminum material in electromagnetic shielding.
[0014] The beneficial effects of the present invention are as follows: the present invention prepares foamed aluminum material by doping alloy elements, metal oxides and viscosity enhancers into aluminum liquid and undergoing a foaming process. The entire preparation process has clear condition parameters and is easy to operate. The obtained foamed aluminum material has the characteristics of light specific gravity, high specific strength, weather resistance and corrosion resistance, long service life, etc. It exhibits excellent electromagnetic shielding performance in a wide band of 10kHz to 40GHz, and can be applied to electronic equipment, communication equipment, aerospace, national defense and military and other fields. DETAILED DESCRIPTION
[0015] In order to make the technical means, creative features, objectives and effects achieved by the present invention easy to understand, the present invention is further described below in conjunction with specific embodiments.
[0016] The present invention provides a foamed aluminum material, comprising the following components in weight percentage:
[0017] Magnesium 3-10%, cerium 0.1-0.2%, neodymium oxide 1-1.5%, boron carbide 0.02-0.1%, silicon 3-8%, carbon 0.02-0.08%, and the balance is aluminum.
[0018] The present invention provides a method for preparing the foam aluminum material, comprising the following steps:
[0019] (1) mixing aluminum oxide and silicon carbide uniformly and then heat treating them in an inert atmosphere;
[0020] (2) heating the aluminum ingot in an inert atmosphere until it is melted, then adding the heat-treated aluminum oxide and silicon carbide, keeping the temperature at 700-800°C for 10-15 minutes, then adding the magnesium ingot, and continuing to keep the temperature at 700-800°C for 10-15 minutes, and finally adding cerium, boron carbide and neodymium oxide, and mixing them thoroughly to obtain an alloy liquid;
[0021] (3) introducing compressed air into the molten alloy liquid, stirring to uniformly distribute the bubbles, then cooling to 650-670° C. at a cooling rate of 5-10° C. / min and keeping the temperature for 10-15 min, and continuing to cool to room temperature to obtain a foam aluminum preform;
[0022] (4) The foam aluminum preform is subjected to a solid solution treatment and an aging treatment to obtain foam aluminum.
[0023] In a further technical solution, the mass ratio of aluminum oxide to silicon carbide is 1:(1-5). The present invention uses nano aluminum oxide and silicon carbide as thickeners, which can increase the viscosity of aluminum liquid, prevent bubbles in aluminum liquid from floating up and agglomerating due to buoyancy, making the size of bubbles uneven, and generating a distribution gradient in the direction of gravity. Adding a thickener can ensure uniform distribution of bubbles.
[0024] In a further technical solution, the inert atmosphere is at least one of argon and nitrogen.
[0025] In a further technical solution, the heat treatment temperature is 500-800°C and the time is 40-60 minutes. The heat treatment can remove the gas and moisture adsorbed on the surface of aluminum oxide and silicon carbide, reduce the impurity gas in the aluminum matrix, and increase the adhesion between aluminum oxide and silicon carbide and the aluminum matrix, thereby improving the mechanical properties of the foamed aluminum.
[0026] In a further technical solution, the aluminum oxide, silicon carbide, cerium, boron carbide and neodymium oxide are all added in powder form.
[0027] In a further technical solution, the pressure of the compressed air is 0.2-0.5 MPa.
[0028] In a further technical solution, the temperature of the solution treatment is 500-600°C and the time is 1-5 hours. The solution treatment can dissolve the added alloying elements in the aluminum matrix lattice, thereby improving the strength of the foamed aluminum while maintaining good plasticity, thereby achieving the purpose of improving the toughness of the foamed aluminum. The distribution of the alloying elements will affect the electromagnetic shielding performance of the matrix, and the heat treatment can improve the electromagnetic shielding performance of the foamed aluminum.
[0029] In a further technical solution, the aging treatment temperature is 20 to 300° C. and the time is 12 to 48 hours. The aging treatment can eliminate the thermal stress generated during the solution treatment in production and improve the fracture strength of the foamed aluminum.
[0030] Furthermore, the aluminum foam is a closed-cell aluminum foam with a porosity of 50-90% and a density of 0.5-1.4 g / cm 3 The diameter of the pores is 3 to 10 mm, and the thickness of the pore walls is 0.2 to 1.2 mm.
[0031] The invention also provides application of the foamed aluminum material in electromagnetic shielding.
[0032] Example 1
[0033] (1) Aluminum oxide and silicon carbide in a mass ratio of 1:1 were uniformly mixed and heat treated in an inert atmosphere (the heat treatment temperature was 500° C. and the time was 40 min).
[0034] (2) The aluminum ingot is heated in an inert atmosphere until it is melted, and then the heat-treated alumina and silicon carbide are added, and the mixture is kept at 700°C for 10 minutes. Then, a magnesium ingot is added, and the mixture is kept at 700°C for another 10 minutes. Finally, cerium, boron carbide and neodymium oxide are added, and the mixture is thoroughly mixed to obtain an alloy liquid.
[0035] (3) Compressed air at a pressure of 0.2 MPa is introduced into the molten alloy liquid, and the bubbles are evenly distributed by stirring. The alloy liquid is then cooled to 650°C at a cooling rate of 5°C / min and kept at this temperature for 10 min. The alloy liquid is then further cooled to room temperature to obtain a foam aluminum preform.
[0036] (4) The foam aluminum preform is subjected to a solution treatment (the solution treatment temperature is 530° C. and the time is 3 h) and an aging treatment (the aging treatment temperature is 20° C. and the time is 24 h) to obtain foam aluminum.
[0037] The aluminum foam material prepared in this embodiment includes the following components in weight percentage:
[0038] Magnesium 3%, cerium 0.1%, neodymium oxide 1%, boron carbide 0.02%, silicon 7%, carbon 0.02%, and the balance is aluminum.
[0039] Example 2
[0040] (1) Aluminum oxide and silicon carbide in a mass ratio of 1:1 were uniformly mixed and heat treated in an inert atmosphere (the heat treatment temperature was 600° C. and the time was 50 min).
[0041] (2) The aluminum ingot is heated in an inert atmosphere until it is melted, and then the heat-treated alumina and silicon carbide are added, and the mixture is kept at 700°C for 10 minutes. Then, a magnesium ingot is added, and the mixture is kept at 700°C for another 10 minutes. Finally, cerium, boron carbide and neodymium oxide are added, and the mixture is thoroughly mixed to obtain an alloy liquid.
[0042] (3) Compressed air at a pressure of 0.2 MPa is introduced into the molten alloy liquid, and the bubbles are evenly distributed by stirring. The alloy liquid is then cooled to 650°C at a cooling rate of 5°C / min and kept at this temperature for 10 min. The alloy liquid is then further cooled to room temperature to obtain a foam aluminum preform.
[0043] (4) The foam aluminum preform is subjected to a solution treatment (the solution treatment temperature is 530° C. and the time is 3 h) and an aging treatment (the aging treatment temperature is 20° C. and the time is 24 h) to obtain foam aluminum.
[0044] The aluminum foam material prepared in this embodiment includes the following components in weight percentage:
[0045] Magnesium 4%, cerium 0.1%, neodymium oxide 1%, boron carbide 0.02%, silicon 3%, carbon 0.02%, and the balance is aluminum.
[0046] Example 3
[0047] (1) Aluminum oxide and silicon carbide in a mass ratio of 1:1 were uniformly mixed and heat treated in an inert atmosphere (the heat treatment temperature was 800° C. and the time was 60 min).
[0048] (2) The aluminum ingot is heated in an inert atmosphere until it is melted, and then the heat-treated alumina and silicon carbide are added, and the mixture is kept at 700°C for 10 minutes. Then, a magnesium ingot is added, and the mixture is kept at 700°C for another 10 minutes. Finally, cerium, boron carbide and neodymium oxide are added, and the mixture is thoroughly mixed to obtain an alloy liquid.
[0049] (3) Compressed air at a pressure of 0.2 MPa is introduced into the molten alloy liquid, and the bubbles are evenly distributed by stirring. The alloy liquid is then cooled to 650°C at a cooling rate of 5°C / min and kept at this temperature for 10 min. The alloy liquid is then further cooled to room temperature to obtain a foam aluminum preform.
[0050] (4) The foam aluminum preform is subjected to a solution treatment (the temperature of the solution treatment is 500° C. and the time is 1 h) and an aging treatment (the temperature of the aging treatment is 100° C. and the time is 48 h) to obtain foam aluminum.
[0051] The aluminum foam material prepared in this embodiment includes the following components in weight percentage:
[0052] Magnesium 4.2%, cerium 0.1%, neodymium oxide 1%, boron carbide 0.02%, silicon 3.6%, carbon 0.02%, and the balance is aluminum.
[0053] Comparative Example 1
[0054] (1) Alumina with a mass ratio of 1:1 is heat treated in an inert atmosphere (the heat treatment temperature is 500° C. and the time is 40 min).
[0055] (2) The aluminum ingot is heated in an inert atmosphere until it is melted, and then the heat-treated aluminum oxide and silicon carbide are added, and the mixture is kept at 700°C for 10 minutes. Cerium, boron carbide and neodymium oxide are added, and the mixture is thoroughly mixed to obtain an alloy liquid.
[0056] (3) Compressed air at a pressure of 0.2 MPa is introduced into the molten alloy liquid, and the bubbles are evenly distributed by stirring. The alloy liquid is then cooled to 650°C at a cooling rate of 5°C / min and kept at this temperature for 10 min. The alloy liquid is then further cooled to room temperature to obtain a foam aluminum preform.
[0057] (4) The foam aluminum preform is subjected to a solution treatment (the solution treatment temperature is 530° C. and the time is 3 h) and an aging treatment (the aging treatment temperature is 20° C. and the time is 24 h) to obtain foam aluminum.
[0058] The aluminum foam material prepared in this embodiment includes the following components in weight percentage:
[0059] Cerium 0.1%, neodymium oxide 1%, boron carbide 0.02%, silicon 7%, carbon 0.02%, and the balance is aluminum.
[0060] Comparative Example 2
[0061] (1) Aluminum oxide and silicon carbide in a mass ratio of 1:1 were uniformly mixed and heat treated in an inert atmosphere (the heat treatment temperature was 800° C. and the time was 60 min).
[0062] (2) The aluminum ingot is heated in an inert atmosphere until it is melted, and then the heat-treated alumina and silicon carbide are added, and the mixture is kept at 700°C for 10 minutes. Then, the magnesium ingot is added, and the mixture is kept at 700°C for another 10 minutes. Finally, cerium is added and mixed thoroughly to obtain a molten alloy.
[0063] (3) Compressed air at a pressure of 0.2 MPa is introduced into the molten alloy liquid, and the bubbles are evenly distributed by stirring. The alloy liquid is then cooled to 650°C at a cooling rate of 5°C / min and kept at this temperature for 10 min. The alloy liquid is then further cooled to room temperature to obtain a foam aluminum preform.
[0064] (4) The foam aluminum preform is subjected to a solution treatment (the temperature of the solution treatment is 500° C. and the time is 1 h) and an aging treatment (the temperature of the aging treatment is 200° C. and the time is 8 h) to obtain foam aluminum.
[0065] The aluminum foam material prepared in this embodiment includes the following components in weight percentage:
[0066] 4.2% magnesium, 0.1% cerium, 3.6% silicon, 0.02% carbon, and the balance is aluminum.
[0067] The electromagnetic shielding performance of the aluminum foam materials prepared in the above embodiments and comparative examples was tested, and the test results are shown in Table 1.
[0068] Table 1 Electromagnetic shielding performance test results of foam aluminum materials
[0069]
[0070]
[0071]
[0072] It can be seen from Table 1 that, compared with Comparative Examples 1 and 2, the foamed aluminum materials prepared in Examples 1 to 3 exhibit excellent electromagnetic shielding performance in a wide band of 10 kHz to 40 GHz.
[0073] The above shows and describes the basic principles and main features of the present invention and the advantages of the present invention. It should be understood by those skilled in the art that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.
Claims
1. A foam aluminum material, characterized in that: The foamed aluminum material comprises the following components in weight percentage: Magnesium 3-10%, cerium 0.1-0.2%, neodymium oxide 1-1.5%, boron carbide 0.02-0.1%, silicon 3-8%, carbon 0.02-0.08%, and the balance is aluminum.
2. The method for preparing the foamed aluminum material according to claim 1, characterized in that: The preparation method comprises the following steps: (1) mixing aluminum oxide and silicon carbide uniformly and then heat treating them in an inert atmosphere; (2) heating the aluminum ingot in an inert atmosphere until it is melted, then adding the heat-treated aluminum oxide and silicon carbide, keeping the temperature at 700-800°C for 10-15 minutes, then adding the magnesium ingot, and continuing to keep the temperature at 700-800°C for 10-15 minutes, and finally adding cerium, boron carbide and neodymium oxide, and mixing them thoroughly to obtain an alloy liquid; (3) introducing compressed air into the molten alloy liquid, stirring to uniformly distribute the bubbles, then cooling to 650-670° C. at a cooling rate of 5-10° C. / min and keeping the temperature for 10-15 min, and continuing to cool to room temperature to obtain a foam aluminum preform; (4) The foam aluminum preform is subjected to a solid solution treatment and an aging treatment to obtain foam aluminum.
3. The preparation method according to claim 2, characterized in that: The mass ratio of the aluminum oxide to silicon carbide is 1:(1-5).
4. The preparation method according to claim 2, characterized in that: The inert atmosphere is at least one of argon and nitrogen.
5. The preparation method according to claim 2, characterized in that: The heat treatment temperature is 500-800° C. and the time is 40-60 minutes.
6. The preparation method according to claim 2, characterized in that: The aluminum oxide, silicon carbide, cerium, boron carbide and neodymium oxide are all added in the form of powder.
7. The preparation method according to claim 2, characterized in that: The pressure of the compressed air is 0.2-0.5 MPa.
8. The preparation method according to claim 2, characterized in that: The temperature of the solution treatment is 500-600°C and the time is 1-5h; The aging treatment is carried out at a temperature of 20 to 300° C. and for a time of 12 to 48 hours.
9. The preparation method according to claim 2, characterized in that: The foam aluminum is a closed-cell foam aluminum with a porosity of 50-90% and a density of 0.5-1.4 g / cm 3 The diameter of the pores is 3 to 10 mm, and the thickness of the pore walls is 0.2 to 1.2 mm.
10. Use of the foamed aluminum material according to claim 1 or the foamed aluminum material obtained by the preparation method according to any one of claims 2 to 9 in the field of electromagnetic protection.
